PENGARUH MEDIA PAPER DOLL TERHADAP PENGETAHUAN SEKSUAL ANAK USIA 5-6 TAHUN DI TK NURUL KHOIR KOTA JAMBI - Dyas Chici Kanora; Nyimas Muazzomi; Sri Indriani Harianja (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Sexual knowledge in early childhood is an essential aspect of children’s development, particularly in fostering awareness of the body and personal boundaries. However, sexual education for young children is often perceived as a taboo topic and is not always delivered using learning media that align with children’s developmental characteristics. This study aimed to examine the effect of paper doll media on the sexual knowledge of children aged 5–6 years at TK Nurul Khoir, Jambi City. This research employed a quantitative approach using a quasi-experimental design with a one group pretest–posttest model. The research participants consisted of 17 children aged 5–6 years. Data were collected through observation using a validated sexual knowledge observation sheet and analyzed using normality tests, homogeneity tests, and a paired sample t-test. The results showed an increase in the mean score of children’s sexual knowledge from 17.706 in the pretest to 29.647 in the posttest, with a mean difference of 11.941. The paired sample t-test revealed a calculated t value of 36.608, which was higher than the t table value of 2.131, indicating that the use of paper doll media had a positive and significant effect on early childhood sexual knowledge. These findings suggest that paper doll media, which are concrete, visual, and role-play–based, are effective learning tools for introducing sexual knowledge to young children in an age-appropriate and developmentally suitable manner.